Global Crude Oil Prices: A Blessing, a Curse, or a Crisis-Driven Force? A New Analysis for Turkey - Oztutus, Ferhat (International Journal of Energy Economics and Policy, 2025)
This paper examines the relationship between global crude oil price volatility (COP) and industrial production (IP) in Turkey, using monthly data from 1986:02 to 2023:12 and applying the time-varying Granger causality (TV-GC) analysis. The empirical results indicate that the causal relationship is highly dynamic, changing over time rather than remaining constant. Specifically, while the FE window results primarily detects causality at the beginning and end of the sample period, the RO and RE windows outcomes suggest a more sustained cause-and-effect relationship. The findings also highlight the importance of diversifying energy sources and adopting economic strategies to mitigate the impact of oil price volatility on industrial production. Turkish policymakers should focus on enhancing energy efficiency, promoting renewable energy investments, and strengthening industrial resilience to external shocks. A deeper understanding of these dynamics can help design new strategies to stabilize industrial output and support sustainable economic growth in Turkey.